2014
DOI: 10.1016/j.steroids.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Role of aldo–keto reductase family 1 (AKR1) enzymes in human steroid metabolism

Abstract: Human aldo-keto reductases AKR1C1-AKR1C4 and AKR1D1 play essential roles in the metabolism of all steroid hormones, the biosynthesis of neurosteroids and bile acids, the metabolism of conjugated steroids, and synthetic therapeutic steroids. These enzymes catalyze NADPH dependent reductions at the C3, C5, C17 and C20 positions on the steroid nucleus and side-chain. AKR1C1-AKR1C4 act as 3-keto, 17-keto and 20-ketosteroid reductases to varying extents, while AKR1D1 acts as the sole Δ4-3-ketosteroid-5β-reductase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
142
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(147 citation statements)
references
References 108 publications
(211 reference statements)
4
142
0
1
Order By: Relevance
“…Key members of this family, AKR1C2 and AKR1D1, are known to bind and metabolize bile acids (43). AKR1D1 in particular catalyzes a key step in bile acid synthesis; deficiency can lead to cholestasis in humans (44).…”
Section: Antiproliferative Mechanism Of Lrh-1 Inhibition Is Conservedmentioning
confidence: 99%
“…Key members of this family, AKR1C2 and AKR1D1, are known to bind and metabolize bile acids (43). AKR1D1 in particular catalyzes a key step in bile acid synthesis; deficiency can lead to cholestasis in humans (44).…”
Section: Antiproliferative Mechanism Of Lrh-1 Inhibition Is Conservedmentioning
confidence: 99%
“…The enzyme of AKR1C2 has the predominant catalytic efficiency. Rižner & Penning (2014) reviewed the possible roles of AKR1 enzymes in human steroid metabolism and alluded on the possibility of AKR1C gene expression in endometrial carcinoma. However, AKR1C1 and AKR1C2 mRNA expression in cancerous endometrium did not differ significantly to that in adjacent control normal tissue (Smuc & Rizner 2009, Sinreih et al 2013.…”
Section: :7mentioning
confidence: 99%
“…Both human AKR1C isoforms, AKR1C1 and AKR1C2 can metabolize dydrogesterone with high efficacy, whereas AKR1C3 is less active (Beranič et al 2011(Beranič et al , 2012. Interestingly, although dydrogesterone is close in structure to progesterone, it is metabolized by AKR enzymes only to 20α-DHD, whereas progesterone is transformed to several products including 5α-pregnane, 5β-pregnane and 4-pregnene metabolites (Rižner & Penning 2014). Recently, Olbrich et al (2016) showed an involvement of cytochrome P450 isozymes in the metabolism of dydrogesterone.…”
Section: Metabolism Of Progestinsmentioning
confidence: 99%
“…In peripheral tissues, AKR1C1 and AKR1C2 form 3β-hydroxytibolone which exhibits estrogenic activity, whereas in liver, TIB is reduced to 3α-hydroxytibolone by AKR1C4 which functions predominantly as 3α-hydroxysteroid dehydrogenase (Steckelbroeck et al 2004). This explains why 3α-hydroxytibolone is the major circulating metabolite, whereas 3β-hydroxytibolone is the major metabolite in target tissues (Penning et al 2014). Interestingly, AKR1C2 exhibits different stereochemical preference depending on the ketosteroid substrate.…”
Section: Metabolism Of Progestinsmentioning
confidence: 99%
See 1 more Smart Citation